(3GdebOeGJ GdeegOGJ deG GbJVJg QShe GdeOhfI ef GdMcGe GdTQYjGJs - (3eMeO Hf CMeO Hf CMeO Hf QTO GdeGdcj GdbQWHj GdCfOdSj, GdbGVj CHh GdhdjO (B( (3GdLO (B)(3, J (B520 (3g` s; (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj, CHh YHO Gddg,J (B191 (3g` s
(3ChdgG (B:s
(3cJGH GdQHG s
(3BNQgG (B:s
(3Edi BNQ GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B10 - (3U (B282 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(1215) s
Keywords: (3Gdabg GdeGdcjs